Efficiency analysis of standard and day 0 superovulatory protocols in Boer breed goats - Grizelj, Juraj; Spoljarić, Branimira; Dobranić, Tomislav; Lojkić, Martina; Dávila, Fernando Sánchez; Samardžija, Marko; Samartzi, Foteini; Getz, Iva; Vince, Silvijo (2017)
ABSTRACT The aim of this research was to investigate the ovarian influence on the success of two superovulatory protocols in goats. Fifteen goats were used twice in the study in a crossover design: once within the control group where standard protocol was applied, and the other time in a modified, day 0 group, where no dominant follicle was present and the follicular cohort was homogenous (“Day 0 protocol”). All the animals were synchronized with vaginal pessaries and superovulated with 6 decreasing doses of pFSH. Although the day 0 protocol significantly decreased the presence of the dominant follicle before the start of the superovulation treatment; it did not improve the superovulatory success. Fifty-four percent of goats in the control group had a dominant follicle which exerted a negative influence on the number of transferable embryos. The other 46% of goats from the same group had a very good superovulatory response, which improved the overall response of the control group in comparison with the day 0 group. Another reason for the lower superovulatory success of the day 0 protocol was the smaller number of second and third category follicles (3.5 - 5.5 mm in size) at the onset of the superovulation protocol, that positively correlated with the number of the transferable embryos (r=0.67; P<0.05). In Boer goats, for the success of superovulatory treatment, the number of follicles of a certain size before the start of the superovulatory treatment has an effect as important as the effect of dominance. The application of the FSH hormone should start at the time when a suitable number of follicles belonging to the second category are present on the ovaries when performing the day 0 protocol. Key words: goat, superovulation, dominant follicle, follicular population, embryo, superovulatory success